PENYELENGGARAN WORKSHOP STRATEGI MENGELOLA TAMAN BACA MASYARAKAT (TBM) DAN KOMUNITAS LITERASI PADA KEGIATAN SASAK LITERATIF 2025 (TEMA: MENYULAM CERDAS, MENULIS KRITIS, MEMBACA DUNIA): Implementation Of A Workshop On Strategies For Managing Community Reading Parks (TBM) And Literacy Communities In The 2025 Literature Sasak Activities (Themes: Smart Embroidery, Critical Writing, Reading The World) - Putra, Sandi Justitia; Mandini, Denda Devi Sarah; Audina, Pin Kharisma; Zulhadi, Zulhadi; Rusyada, Gozin Najah; Husbuyanti, Irma El-Mira; Rahmandari, Ismi Arifiana; Brajamusti, Fendi; Susanto, Agus; Himadila, Sukmarani; Febian, Rosa (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
This community service activity was carried out to address various challenges faced by Community Reading Parks (TBM) and literacy communities in North Lombok Regency, particularly related to weak managerial capacity, lack of program innovation, and minimal partnership networks. The main objective of this service is to improve the capabilities of TBM managers and literacy communities in institutional management, sustainable program development, and the use of digital media to promote literacy. The implementation method was carried out through a participatory approach that included interactive lectures, group discussions, experiential learning, work plan preparation simulations, and evaluation through pre- and post-tests. The activity, attended by 40 participants, resulted in increased competency in understanding the principles of TBM governance, developing needs-based programs, and strategies for strengthening collaboration between institutions. In addition, participants successfully developed a simple work plan as an initial step in strengthening the village literacy ecosystem. The results of theservice demonstrate that the participatory mentoring model is effective in encouraging the independence of literacy communities and strengthening the grassroots literacy movement in North Lombok.